Impact of dietary Biocide clay on growth, physiological status, and histological indicators of the liver and digestive tract in Nile tilapia (Oreochromis niloticus) - Asmaa S. Abd El-Naby; Amel M. El Asely; Mona N. Hussein; Abd El-Rahman A. Khattaby; Haitham G. Abo-Al-Ela (Scientific Reports)
Abstract This study evaluated the effects of Biocide, containing silicon tetrahedrons and organic acids, on growth performance, feed utilization, immune response, and oxidative status in Nile tilapia (Oreochromis niloticus). A total of 300 Nile tilapia fingerlings (initial weight: 3.55 ± 0.01 g) were distributed across 15 tanks and fed diets containing 0.0 (control), 0.25, 0.5, 1, and 2 g kg⁻¹ Biocide for 90 days, with three replicate tanks per treatment. Biocide is enriched with organic acids (fumaric acid and citric acid) and amino acids (glutamine, tyrosine, methionine, serine, and threonine). Fish fed Biocide-supplemented diets demonstrated significantly improved growth performance, with the highest weight gain, feed conversion ratio, and protein efficiency ratio observed in the 1 g kg⁻¹ group. Survival rates did not differ significantly among treatments. Whole-body crude protein content peaked in the 1 g kg⁻¹ group, while moisture, lipid, and ash contents remained unchanged. Hematological parameters, including red blood cell count, hemoglobin concentration, and packed cell volume, improved significantly. Serum lipid profiles showed reduced cholesterol, triglycerides, low-density lipoprotein, and very-low-density lipoprotein levels, alongside increased high-density lipoprotein levels, particularly in the 1 g kg⁻¹ group. Antioxidant enzyme activities (catalase, glutathione peroxidase) and total antioxidant capacity were significantly elevated in the liver and intestine, while malondialdehyde levels decreased. Digestive enzyme activities (amylase, lipase, and protease) were markedly enhanced. Histopathological analysis revealed improved liver, stomach, and intestinal morphology, including increased mucous secretion and enhanced intestinal villi structure, in fish fed 1 g kg⁻¹ Biocide. In conclusion, Biocide supplementation, particularly at 1 g kg⁻¹, significantly improved growth performance, feed utilization, immune function, and antioxidant capacity in Nile tilapia. Notably, the findings highlight Biocide’s primary mode of action on gut health, underscoring its potential as a dietary additive for improving aquaculture productivity.